Chemical composition, antibacterial and antioxidant activities of acetone extract from the branches and leaves of Jasminum annamense subsp. annamense (Oleaceae) - Van, Hong Thien; Ngo, Ngoc Hung; Nguyen, Ngoc Thuan; Nguyen, Ngoc An; Pham, Tan Viet; Nguyen, Hanh Thi Dieu; Thieu, Gia Linh; Dang, Thi Hoai Thuong; Nguyen, Quoc Hung; Le, Thanh Tho; Le, Van Son; Dam, Sao Mai (Journal of Phytology, 2022)
Jasminum annamense subsp. annamense is a rare subspecies of Jasminum annamense belonging to the Oleaceae family. The aims of this study were to address the chemical profiles, antibacterial and antioxidant activities of acetone extract isolated from branches and leaves Jasminum annamense subsp. annamense for the first time. The chemical constituents of acetone extracts of studied samples were investigated by gas chromatography-mass spectrometry. There were a total of 24 components identified from the leaf extract, including lup-20(29)-en-3-one (27.93%), levodopa (19.68%), trans-cinnamic acid (7.58%), linolenic acid (6.35%) as the major compounds. Meanwhile, 26 components were reported from the branch extracts which are sorbitol (25.74%), lupeol (13.3%), cis-vaccenic acid (6.97%), glycerin (6.35%) and n-hexadecanoic acid (5.86%) were the main components. The two acetone extracts of J. annamense subsp. annamense exhibited antibacterial effect against Bacillus cereus, Escherichia coli, Salmonella enteritidis and Staphylococcus aureus based on disk diffusion assay. In addition, leaf and branch extracts of the studied species also display notable antioxidant activity in the ABTS assay with IC50 values of 311.75±3.39 and 664.46±3.732 µg/ml, respectively. This is the first report on the chemical and biological properties of J. annamense subsp. annamense and provides a promising perspective for developing good sources of antioxidant and antimicrobial compounds against both Gram positive and negative bacteria.